2015
DOI: 10.1519/jsc.0000000000000631
|View full text |Cite
|
Sign up to set email alerts
|

Quantification of Training Load, Energy Intake, and Physiological Adaptations During a Rugby Preseason

Abstract: Rugby Union (RU) is a high-speed collision sport consisting of an intermittent activity profile. Given the extreme physical demands of the sport, significant emphasis is placed on players possessing high lean body mass while minimizing body fat. Anecdotally, the most significant changes in body composition are observed during the preseason; however, there are no objective data on the physiological demands and energy intake during this time. We therefore monitored 45 elite European RU players over the 10-week p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

14
121
7

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 78 publications
(142 citation statements)
references
References 34 publications
14
121
7
Order By: Relevance
“…To conclude, we report average weekly TEE values of ~22.5 MJ in professional RL players that are higher than reported previously in RU players (Bradley et al, 2015a;Bradley et al, 2015b). We speculate that this high TEE reflects the ability of DLW to "The Assessment of Total Energy Expenditure During a 14-day 'In-Season' Period of Professional Rugby League Players Using the Doubly Labelled Water Method" by Morehen JC et al International Journal of Sport Nutrition and Exercise Metabolism © 2016 Human Kinetics, Inc. assess all aspects of rugby activity, including the physical collisions that have previously not been examined.…”
Section: Kg)contrasting
confidence: 59%
See 1 more Smart Citation
“…To conclude, we report average weekly TEE values of ~22.5 MJ in professional RL players that are higher than reported previously in RU players (Bradley et al, 2015a;Bradley et al, 2015b). We speculate that this high TEE reflects the ability of DLW to "The Assessment of Total Energy Expenditure During a 14-day 'In-Season' Period of Professional Rugby League Players Using the Doubly Labelled Water Method" by Morehen JC et al International Journal of Sport Nutrition and Exercise Metabolism © 2016 Human Kinetics, Inc. assess all aspects of rugby activity, including the physical collisions that have previously not been examined.…”
Section: Kg)contrasting
confidence: 59%
“…al., 2015) and potentially improve recovery from the weekly muscle soreness (Fletcher et al, 2015) by ensuring adequate post-game nutrition is prescribed. Although some studies have attempted to quantify TEE in elite Rugby Union (RU) players (Bradley et al, 2015a;Bradley et al, 2015b) and elite RL players (Coutts et al, 2003) these studies are somewhat limited by the methods employed. For example, Bradley et al (2015a) utilised Sensewear armbands that cannot be worn during games or physical collisions and therefore these data fail to account for the demands of match day competition and collision-focused training sessions that could contribute a significant amount to the TEE.…”
Section: Introductionmentioning
confidence: 99%
“…Although Bradley et al (2014) have reported the training demands and nutritional intakes of an elite RU pre-season, to date there are no studies showing the training demands and EIs and EEs during the competitive season. Due to the importance of competitive performance, these data would be of great significance to the strength and conditioning professional to allow informed decisions to be made with regards to players' diets during this competitive period.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the habitual protein intake of the participants is not commonly reported, which is important as protein gastric emptying and satiety response has been demonstrated to have a reduced effect on individuals with high habitual protein intakes (Long, Jeffcoat, & Millward, 2000;Shi et al, 1997). There is evidence to suggest that many athletes already consume protein above the current recommendations (Rodriguez, Di Marco, & Langley, 2009); in the range of~1.5-2.5 g·kg day −1 (Bradley et al, 2015;Cole et al, 2005;Lundy, O'Connor, Pelly, & Caterson, 2006;Schokman, Rutishauser, & Wallace, 1999), and therefore may have a differing satiety response to supplemental protein than non-athletes or individuals with lower protein intakes. Therefore, this study will assess the impact of a manipulation of protein dose (20, 40, 60 and 80 g) in a liquid whey protein supplement on subjective sensations of appetite and food intake in a cohort of concurrently training athletes who consume protein in excess of current recommendations (Rodriguez et al, 2009).…”
Section: Introductionmentioning
confidence: 99%